PENGARUH PENATAAN RUANG KOTA TERHADAP TINDAKAN KRIMINAL MALAM HARI DI KORIDOR JALAN SETURAN RAYA, YOGYAKARTA - , JATI PRAMONO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
There is no doubt that night-time spaces give great influence to the development of cities in Indonesia, especially in terms of social, economic, and cultural communities. But on the other hand, it is also synonymous with criminal acts such as alcohol consumption, vandalism, prostitution and others. Therefore this study focuses on the correlation between the use of spaces in the evening against the risk of crime, especially in Indonesia. The understanding about the conditions of urban setting in Indonesia and its correlation to night crime becomes so substantial, mainly as references to urban spatial planning in the neighborhood scale. The approach chosen in this study is qualitative approach. This approach was chosen because this study attempted specifically to find the relationship between the variables shows the real spatial situations and aims to describe the conditions that lie behind them. This study focuses on efforts to reduce the impact of crime of a night-time spaces through spatial approaches and urban design principles. The result indicates that there is a relationship between physical environment variables with the risk of crime. The results also indicate there are at least four most dominant variable in affecting the risk of criminal prosecution. The four variables are lighting, accessibility, surveillance and land use mix.